Smartphone addiction reduction: effectiveness of print and social media education - Robert Shen; Elisabeth Rukmini (Intelektual Pustaka Media Utama, 2023)
Smartphone usage dependency in daily activities also causes vulnerability to addiction and its effects on health, especially the increment during the COVID-19 pandemic because of the switching activities to online. Research on the prevention and treatment to overcome smartphone addiction is still relatively limited. This study aims to analyze the effectiveness of educational media programs using social-media compared to printed-media in reducing smartphone addiction levels. Changes in interpersonal-relationship and self- esteem as a related mediator and affected negative impacts of smartphone addiction were also investigated. Media effectivity was assessed by the decrease of users’ addiction level, and affected interpersonal-relationship and self-esteem. A three-wave cross-sectional series conducted on 54 subjects, divided into two groups were given the routine printed or social-media educational program for a month. Results from comparative analysis showed printed-media is more effective than social-media in reducing smartphone addiction; both are statistically significant (p=0.000). It shows that health education has a role in smartphone addiction prevention, but choosing the right and most effective media for specific populations is necessary. Both groups increased interpersonal-relationship, but self-esteem rose only in the printed-media group. Interpersonal-relationship tended to increase, while self- esteem varied from person to person, showing the addiction level might affect mental-behavioral health but still need further analysis of other influencing confounding factors.